Functional Shocks to Inflation Expectations and Real Interest Rates and Their Macroeconomic Effects - Christina Anderl; Guglielmo Maria Caporale (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper applies a recently developed method (Inoue and Rossi, 2021) to estimate functional inflation expectations and ex-ante real interest rate shocks, and then examines their macroeconomic effects in the context of a Functional Vector Autoregressive model with exogenous variables (Functional VARX). Monthly data from January 1998 to May 2023 for the US, the UK and the euro area are used for the analysis. The estimated impulse responses show significant effects of the functional shocks on both inflation and output. In addition, threshold functional local projections indicate that the effects are nonlinear and depend on central bank credibility. Further, inflation expectations shocks have similar effects to supply (demand) ones when they are driven by long-term (short-term) changes. In the presence of an inverted (steepening) real interest rate term structure, the effects are inflationary (deflationary) and expansionary (recessionary). Finally, the responses of inflation, output and the policy rate are driven primarily by the slope and curvature factors of the term structure shocks, which contain important information not captured by traditional scalar shocks.
Keywords: E31; E43; C32; 330; inflation expectations; term structure; real interest rates; functional shocks